1988
DOI: 10.1254/jjp.47.433
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulating effect of neurotropin on delayed type hypersensitivity response in mice.

Abstract: Abstract-Effectof Neurotropin on the delayed type hypersensitivity (DTH) response to sheep red blood cells was examined in mice. Neurotropin suppressed the high DTH responses in ddY and BALB/c mice, while it enhanced the low DTH response in C57BL/6 mice when administered after sensitization. In addition, Neurotropin exerted a suppressive effect on the enhanced DTH response by cyclophosphamide pretreatment in C57BL/6 mice, but had a restorative effect on the suppressed DTH response in ddY mice loaded with restr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Since mice that received 50 or 100 NU / kg Neurotropin did not show any augmented response, 80 NU / kg Neurotropin might be an optimal dose. Actually, the dose-response curve of Neurotropin has showed a bellshaped in some experiments (19,22,31).…”
Section: Discussionmentioning
confidence: 99%
“…Since mice that received 50 or 100 NU / kg Neurotropin did not show any augmented response, 80 NU / kg Neurotropin might be an optimal dose. Actually, the dose-response curve of Neurotropin has showed a bellshaped in some experiments (19,22,31).…”
Section: Discussionmentioning
confidence: 99%
“…Yanagihara et al (2,3) described that NSP recovered the immune function in mice suppressed by mitomycin C-treatment or irradiation. Yoshii et al (4,5) demonstrated that NSP enhanced delayed type hypersensi tivity (DTH) against sheep red blood cells in low responder C57BL/6 mice through the induction of Lyt-1 +2 DTH helper T cells, and it also enhanced the DTH in mice suppressed by loading with restraint stress. These findings suggest that NSP has immunostimulating/ immunomodulating activity in addition to anti-allergic activity.…”
mentioning
confidence: 99%